2018
DOI: 10.24191/mar.v17i3.796
|View full text |Cite
|
Sign up to set email alerts
|

Entertainment Gratification, Informative Gratification, Web Irritation and Self-Efficacy as Motivational Factors to Online Shopping Intention

Abstract: The Internet technology and pervasive computing has provided consumers with privileges to shop online. In addition, the Industry 4.0 agenda has placed the business web and the social web as the ecosystem domains, which explains why online shopping is a norm today. While many studies have been conducted to investigate the determinants of consumers’ intention to use online shopping, mixed results are always found, especially when the business take unique approaches for their digital presence. Besides, even thoug… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(7 citation statements)
references
References 9 publications
0
5
0
Order By: Relevance
“…H2: There is a positive relationship between the IG and the consumers' PI Information Gratification does indeed have a positive influence on the consumers' purchase intentions (Samsudin and Ahmad, 2014;Harshini, 2015;Zamzuri et al, 2018). Not only that results from this paper also finds that information gratification through Live Stream shopping is the leading factor that influences the purchase intentions of the consumers.…”
Section: Information Gratificationmentioning
confidence: 56%
“…H2: There is a positive relationship between the IG and the consumers' PI Information Gratification does indeed have a positive influence on the consumers' purchase intentions (Samsudin and Ahmad, 2014;Harshini, 2015;Zamzuri et al, 2018). Not only that results from this paper also finds that information gratification through Live Stream shopping is the leading factor that influences the purchase intentions of the consumers.…”
Section: Information Gratificationmentioning
confidence: 56%
“…To understand Chinese consumers' live-stream shopping intentions, Ma (2021) surveyed 339 of them and established that hedonic gratification was a significant indicator of purchase intentions on those platforms. Research on the motivational factors of online shopping intention among 217 young executives who are frequent online shoppers showed that there was a significant relationship between entertainment gratification and online shopping continuous intention because online consumers would have favorable attitudes toward the platform if it offered them rewarding entertainment (Zamzuri et al, 2018). Chang et al (2020) determined that information completeness was deemed essential for consumers to be able to scrutinize the relative benefits and relevance of the messages on online commerce platforms owing to the constant bombardment of asymmetrical information.…”
Section: Entertainment Gratificationmentioning
confidence: 99%
“…A specific reference to the problem of age appears in works devoted to the specificity of generations, especially the young (millennials, generations Y and Z). These issues are addressed by Aw et al (2021), Dabija & Lung (2018), Makhitha (2014), Melović et al (2021), Svatosova (2022) and Zamzuri et al (2018). College and university students attract particular attention from researchers as a sub-generation group, as in Al Asheq et al (2022), Hossain et al (2020), Mehrotra et al (2020), Ofori & Appia-Nimo (2019) and Seock & Bailey (2008).…”
Section: Literature Reviewmentioning
confidence: 99%